ANTI-FERTILITY EFFECTS OF DIFFERENT FRACTIONS OF ANETHUM GRAVEOLENS L. EXTRACTS ON FEMALE RATS - Malihezaman, Monsefi; Mojaba, Masoudi; Elham, Hosseini; Farnaz, Gramifar; Ramin, Miri (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Our previous studies showed the effects of aqueous and ethanol extracts of Anethum graveolens L. (dill) on female infertility. In the present study we investigated whether different fractions of this herb extract can cause infertility in rats. Female rats were divided into the control groups, the groups receiving either a low (0.5 g/kg)) or a high dose (5g/kg) of water, N-butanol, chloroform and ether fractions of the aqueous plant extract, and the groups receiving either a low (0.045 g/kg) or a high dose (0.45 g/kg) of the same fractions of ethanol extract. The mentioned doses were gavaged in 1mL for 10 days. Vaginal smears were prepared daily. Estradiol and progesterone levels were measured. The left oviduct and ovary were removed, their tissue subsequently being prepared in form of histology slides and stained using haematoxylin-eosin and Masson’s trichrome. Female rats assigned to each group were mated with males; after that, crown-rump lengths and weights of newborn rats were measured. Results showed that each fraction produced some changes such as hormonal level reduction (chloroform fraction), diestrus phase prolongation and infertility (water fraction), and increase in pregnancy duration (chloroform and ether fractions). We concluded that each fraction comprises only some of the mentioned components and therefore recommended the usage of crude extract, especially the aqueous one, in case infertility aims to be induced.